Margin-o-polis (2008)
A strong feeling of uncertainty and discomfort grasps a big group of population marginalized in economic, space, environmental, political, normative and cultural ways all over Colombia, Latin America and the “underdeveloped countries”, countries that during decades have witnessed and taken part in the most important transformations of the urban planet without being able to attain the social benefits that their citizenship condition should allow them to. The article presents a particular vision of a universal phenomenon and looks out to manage the debate in the direction of one renewed denomination of itself.